Injection of ropivacaine combined with pregabalin in a patient with post-traumatic trigeminal neuropathic pain - Tisné-Versailles Sophie; Fénélon Mathilde; Marteau Jean-Marie; Catros Sylvain; Fricain Jean-Christophe (EDP Sciences, 2018)
Introduction: Post-traumatic painful trigeminal neuropathy is a chronic facial pain secondary to trigeminal nerve injury. The treatment of this pain is a therapeutic issue due to the alteration of quality of life that it generates. Observation: A 58-year-old man whose main history of facial trauma has been consulted in the Odontology Department for bilateral trigeminal neuropathic pain that has been evolving for several months. The interrogation revealed continuous pain like electric shocks in the canine areas and daily painful exacerbations. Hyperesthesia and allodynia were found on clinical examination. The patient had received several treatments, oral and local, without significant improvement. As a last resort, injections of ropivacaine every 2 weeks associated with pregabalin (200 mg/day) were performed. At 6 months, there was a clear decrease in the burning sensation and a complete disappearance of painful exacerbations. Discussion: Two studies have recently shown the benefit of the combination of an antiepileptic and a local analgesic in the treatment of classical trigeminal neuralgia, justifying their use in a context of post-traumatic neuropathic pain. Conclusion: Further studies with higher levels of evidence are needed to confirm these preliminary results.